Cyberbullying among University Students: A Study on Bangladeshi Universities - Fakir, Md Kawshar Jahan (Journal of Social, Humanity, and Education, 2023)
Purpose: The study aimed to disclose the factors which directly and/or indirectly influence cyberbullying among university students and to find solutions and/or provide suggestions about overcoming cyberbullying among university students. Methodology: The study's goal is to identify the factors that influence cyberbullying among university students. The research team collected 202 data points through a seven-point Likert scale questionnaire. A descriptive research methodology was used for this study. The sampling method was probability. The descriptive statistics analysis, reliability testing, and regression analysis were all carried out using the SPSS 26.0 Version. Results: All of the independent variables, including social influences, use of social media, internet addiction, social anxiety, and trait anger, have a positive impact on cyberbullying. Limitations: The study used only five variables and focused on Bangladeshi university students as a sample. Contribution: This research will help to understand cyberbullying and raise awareness about it among students, authorities, the government, and other interested parties, as well as provide recommendations to students on how to stay safe online and prevent cyberbullying among them.